Mengembangkan Kemampuan Mahasiswa dalam Memvalidasi Bukti pada Aljabar Abstrak melalui Pembelajaran Berdasarkan Teori APOS - I Made Arnawa (Jurnal Matematika & Sains, 2009)
This is an experimental study using control group pretest posttest design. The experiment group is treated using APOS theory instructional. The control group is treated using conventional/traditional mathematics instruction (TRAD). The main purpose of the study is to analyze the contribution of APOS in developing student ability to validate proof in Abstract Algebra. This experiment involves 180 students as research subjects from two different universities that is department of mathematics UNAND and department of mathematics educations UNP. The data was gathered by proof validated test. Based on the result of data analysis, the main result of this study is: ability in proof validated of students in APOS group is significantly better than the students in TRAD group.